Penerapan Akuntansi Sektor Publik Dan Pengawasan Terhadap Kualitas Laporan Keuangan Dan Implikasinya Terhadap Akuntabilitas Kinerja Instansi Pemerintah Jawa Timur - Oktavianto, Muhammad Rendi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Good governance has principles of effective finance, because quality financial reporting creates accountability for public institutions. In order to preserve responsibility for the performance of government agencies in East Java, this study aims to understand how public sector accounting is employed, how financial report quality is checked, and how these elements interact. Surveys and library research are utilized as data gathering methods in the descriptive quantitative research methodology. Meanwhile, the object of this study is the Regional Apparatus Organization (OPD) in East Java. The results of the study found that the application of public sector accounting and supervision has an impact on the accuracy of financial reports and the consequences are for holding government entities accountable for their performance. Accountability for how well government institutions function is very important for the creation of good governance and can be demonstrated by the quality of financial reports with good accounting discipline. Thus, the importance of the application of public sector accounting and supervision of the accuracy of financial reports and implications for the accountability of government agencies for their performance.